Pak Choi (Brassica rapa ssp Chinensis L) quality response to pre-harvest salinity and temperature - Mahmud, TMM; Atherton, JG; Wright, CJ; Ramlan, MF; Ahmad, SH (Wiley, 1999)
The effects of pre-harvest salinity levels (1.7, 9.5 and 12.3 mS cm-1) and temperatures (18, 21 and 25°C) on the ascorbic acid and total chlorophyll contents of Pak Choi (Brassica rapa ssp. Chinensis L) were investigated. The relationships of these chemical contents with storage period (0, 7 and 14 days) and water loss were also monitored. Increased production temperatures significantly (p < 0.001) reduced the ascorbic acid and total chlorophyll (p < 0.01). Ascorbic acid content in leaves grown at various salinities was significantly (p < 0.01) reduced beyond 9.5 mS cm-1. Total chlorophyll was not affected by these different levels of salinity. Ascorbic acid contents of harvested shoots fell rapidly during the first seven days of storage, most markedly in shoots taken from plants grown at high salinity. The pattern of chlorophyll degradation depended on the plants' production environment where higher temperatures resulted subsequently in rapid degradation during storage. For shoots grown at high salinity, the chlorophyll content was sustained during early storage. Linear relationships were apparent between water loss and ascorbic acid and total chlorophyll contents of shoots from the range of treatments.